The Physicochemical and Rheological Properties of Green Banana Flour–Wheat Flour Bread Substitutions - Yasmeen M. Bashmil; Frank Bekes; Michael Ruderman; Hafiz A. R. Suleria; Rudi Appels; Frank R. Dunshea (Plants)
Functional foods are currently receiving increasing popularity in diet modification. Green bananas contain far more dietary fiber (DF) and resistant starch (RS) than mature bananas. The potential for integrating these vital components into food, such as bread, has expanded. Thus, this study aimed to examine the physicochemical and rheological behavior of wheat flour dough after the addition of varying amounts of Australian, green banana flour (GBF) substitutions (5, 10, 15, 25, and 30%). Using MixoLab 2, we recorded the rheological parameters of the dough that had GBF substitutions. Additionally, the flour color (‘L*’, ‘a*’, and ‘b*’ value) and crumb cell structure analysis were evaluated. Although increasing the amount of GBF replacement generally improved dough quality with all banana cultivars, GBF from Cavendish and Ladyfinger showed a greater improvement than Ducasse. Improved dough mixing stability and increased viscosity, starch gelatinization, and retrogradation were all predicted to contribute to longer bread shelf life. RS content of the enriched bread increased significantly with both Ladyfinger and Ducasse (2.6%), while Ladyfinger bread had the highest DF (9.1%). With increasing GBF, L*, a*, and b* values were changed considerably with a strong linear correlation. A MATLAB analysis indicated substantial variations across samples regarding the small, medium, and total air space counts based on 10% banana flour as a standard level of addition. In conclusion, the processing properties and nutritional value of wheat flour can be enhanced by replacing specific proportions of wheat flour with green banana flour without major detrimental effects on dough processing attributes and thus highlight the possibility of utilizing GBF from different banana varieties for use in fine-tuning composite flour developments.